PSYCHOLOGICAL CAPITAL DAN WORK ENGAGEMENT: KONTRIBUSI HOPE, OPTIMISM, RESILIENCE DAN EFFICACY TERHADAP WORK ENGAGEMENT - Mardiah Mardiah; Zaki Nur Fahmawati (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Recently, market demand in the coal mining industry has increased, so companies need to pay attention to HR productivity as one of the important factors to meet market targets. Company